Polish banking industry efficiency: a DEA window analysis approach - Kisielewska, Magdalena; Guzowska, Malgorzata; Nellis, Joseph G.; Zarzecki, Dariusz (Cranfield University School of Management, 2007)
The Polish banking industry has been transformed since the country’s transition to a market economy which began at the end of the 1980s. The industry has now developed and expanded to encompass more than 60 participants and it can thus be described today as a relatively competitive market. Against this background, this paper evaluates the financial performance of the industry over time, based on the ten largest Polish banks that represent around 80 percent of the total sector in terms of assets. In particular, cost efficiency of the banks is analyzed on the basis of six production models. Efficiency scores are obtained using Data Envelopment Window Analysis between 1995-2003 period, using intertemporal and locally intertemporal data. Productivity changes within the sector are investigated using the Malmquist Index approach.
Keywords: DEA window analysis; Malmquist index; Efficiency; Polish banking